(untitled) (Texas Journal of Medical Science, 2024)
Retrospective assessment of clinical signs and course of the disease in patients with osteoarthritis in the sex ratio. Materials and Methods: In this scientific study, a retrospective analysis of 300 patients hospitalized in the City Clinical Hospital No. 3 from 2015 to 2019 was carried out based on medical records, with an emphasis on the analysis of the clinical course and consequences of the disease. Results: On the basis of the obtained data on x-ray images, the articular syndrome and joint structure disorders observed in patients with osteoarthritis (OA) were assessed. Conclusions: It was noted that in patients with OA, the articular syndrome was different and gender differences were found in the course of the disease.